Impact of High School Directors’ Digital Leadership Practices on Teachers’ Self-Efficacy: A Case Study in Phnom Penh, Cambodia - Kim, Seila; Mok, Sarom; Lim, Sothea; Em, Sereyrath (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: This study aims to investigate the impact of high school directors’ digital leadership practices on teachers’ self-efficacy in Phnom Penh, Cambodia. Methodology: This study employed a quantitative survey design, utilizing an online questionnaire. The sample included 300 teachers from 30 high schools in Phnom Penh City. Data analysis was conducted with SPSS version 30, employing both descriptive and inferential statistical methods to answer the research questions. Main Findings: Findings show that both high school directors’ digital leadership practices and teachers’ self-efficacy, overall and by dimensions, were at high levels. A weak but significant positive correlation was found between digital leadership practices and teachers’ self-efficacy. The results also suggest that strengthening digital leadership can indirectly enhance teaching standards by boosting teachers’ self-efficacy. Novelty/Originality of this Study: This study contributes new knowledge by empirically linking digital leadership practices of school directors with teachers’ self-efficacy in Cambodia’s secondary education sector. It advances existing research by highlighting the contextual role of digital leadership in improving teacher capacity, offering practical insights for policymakers and school leaders to develop targeted leadership and training programs.